Biznes, kryzys, etyka. Zło gospodarcze jako przedmiot nazywania - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2011)
Facing the economic crisis (began in 2007) managers and political leaders pay more attention to the postulate of socially responsiblebusiness. The axiological turn gives new possibilities to implement ethical standards in the sphere of economy. Alas, at the same time, thistask evokes the following problems. Firstly, as social researchers, we need to know how to compose heterogeneous axiological systems(to join rules of ethics with the imperative of economic efficiency). Secondly, as market participants, we have to find the formula of mutualunderstanding (being seen as precondition of our ethical claims).